Overcoming Difficulties in Managing Online Learning in the Era of the Covid-19 Pandemic - Khairiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
Difficulties overcoming the management of online learning in the era of the Covid-19 pandemic, due to the level of availability of technological devices, the readiness of human resources, the level of technological literacy of teachers, students and parents and the readiness of educational institutions. This article uses a descriptive qualitative method, this paper aims to map the forms of efforts to overcome online learning difficulties during the co-19 pandemic and analyze the causes. Data collected sourced from primary data and secondary data. Secondary data of 50 Aliyah madrasah institutions in Bengkulu. Primary data includes teacher profiling, motivation, types of difficulties and efforts to overcome the difficulties they experience. Secondary data consists of teacher literacy and attendance, statistics on teacher competency test results. Primary data and secondary data are used as a basis for analysis in efforts to overcome difficulties in managing online learning during the co-19 pandemic, through interviews with 15 teachers and 15 students, taking into account their special characteristics, situation and culture. This study shows that differences in socioeconomic groups of students and parents shape their opportunities to study online. The gap in students' socio-economic class has consequences for the level of difficulty in managing online learning in communicating, responding, doing activities, collaborating and achieving student competency and achievement. The existing structural gaps are an important factor in interpreting the reality of difficulties in managing online learning at Aliyah madrasas in Bengkulu Province, Indonesia.